2020
DOI: 10.1038/s41598-020-78575-w
|View full text |Cite
|
Sign up to set email alerts
|

Death by SARS-CoV 2: a Romanian COVID-19 multi-centre comorbidity study

Abstract: Evidence regarding the relation between SARS-CoV-2 mortality and the underlying medical condition is scarce. We conducted an observational, retrospective study based on Romanian official data about location, age, gender and comorbidities for COVID-19 fatalities. Our findings indicate that males, hypertension, diabetes, obesity and chronic kidney disease were most frequent in the COVID-19 fatalities, that the burden of disease was low, and that the prognosis for 1-year survival probability was high in the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 30 publications
4
36
1
2
Order By: Relevance
“…Among the first 147 COVID-19 cases in Romania, 88 were imported cases, with 64 from Italy [12]. At the first release of the present survey, there were around 9000 cases, more than 40,000 people quarantined at home, and more than 500 deaths from COVID-19 [14]. Even if many distancing rules were maintained for almost the entire year, including schools closing [15], the social pressure made it impossible and unreasonable to reimpose strict measures as in the beginning of the pandemic.…”
Section: Perspectives On Covid-19 Prevention and Knowledgementioning
confidence: 65%
See 1 more Smart Citation
“…Among the first 147 COVID-19 cases in Romania, 88 were imported cases, with 64 from Italy [12]. At the first release of the present survey, there were around 9000 cases, more than 40,000 people quarantined at home, and more than 500 deaths from COVID-19 [14]. Even if many distancing rules were maintained for almost the entire year, including schools closing [15], the social pressure made it impossible and unreasonable to reimpose strict measures as in the beginning of the pandemic.…”
Section: Perspectives On Covid-19 Prevention and Knowledgementioning
confidence: 65%
“…In Romania, the first case of SARS-CoV-2 infection was confirmed on 26 February 2020, a contact of an Italian citizen [13], and, 1 month later, on 22 March 2020, the first COVID-19 death was noted [14]. Among the first 147 COVID-19 cases in Romania, 88 were imported cases, with 64 from Italy [12].…”
Section: Perspectives On Covid-19 Prevention and Knowledgementioning
confidence: 98%
“…The simulations of the measures' effects in containing the virus spread in Romania below were made in AnyLogic 8, based on a data set that should be adjusted and adapted to different regions. As input, the model uses the Romanian population divided into three age groups: 0-19, 20-59, and 60 years or older, according to national severity profiles which show a higher incidence of severe COVID-19 cases and deaths in the 60+ age group, due to existing comorbidities (59). The number of days between being infected to becoming infectious is, on average, 5.1 days (60,61), and the time being infectious 5.0 (62).…”
Section: The Choice Of An Epidemiological Modelmentioning
confidence: 99%
“…In this way, chronic inflammation in vessel structure is a pathological process that acts as a crucial contributor to the development of hypertension [ [19] , [20] , [21] ]. Investigations have reported that hypertension, diabetes, and cardiovascular diseases were the most prevalent comorbidities among patients with COVID-19, in which hypertension appeared consistently as the most prevalent risk factor [ [22] , [23] , [24] , [25] ].…”
Section: Figmentioning
confidence: 99%